Reconstruction of Hyaline Cartilage Deep Layer Properties in 3-Dimensional Cultures of Human Articular Chondrocytes. Issue 6 (26th June 2014) - Nanduri, Vibudha; Tattikota, Surendra Mohan; T., Avinash Raj; Sriramagiri, Vijaya Rama Rao; Kantipudi, Suma; Pande, Gopal
Background: Articular cartilage (AC) injuries and malformations are commonly noticed because of trauma or age-related degeneration. Many methods have been adopted for replacing or repairing the damaged tissue. Currently available AC repair methods, in several cases, fail to yield good-quality long-lasting results, perhaps because the reconstructed tissue lacks the cellular and matrix properties seen in hyaline cartilage (HC). Purpose: To reconstruct HC tissue from 2-dimensional (2D) and 3-dimensional (3D) cultures of AC-derived human chondrocytes that would specifically exhibit the cellular and biochemical properties of the deep layer of HC. Study Design: Descriptive laboratory study. Methods: Two-dimensional cultures of human AC–derived chondrocytes were established in classical medium (CM) and newly defined medium (NDM) and maintained for a period of 6 weeks. These cells were suspended in 2 mm–thick collagen I gels, placed in 24-well culture inserts, and further cultured up to 30 days. Properties of chondrocytes, grown in 2D cultures and the reconstructed 3D cartilage tissue, were studied by optical and scanning electron microscopic techniques, immunohistochemistry, and cartilage-specific gene expression profiling by reverse transcription polymerase chain reaction and were compared with those of the deep layer of native human AC. Results: Two-dimensional chondrocyte cultures grown in NDM, in comparison with those grown in CM, showed more chondrocyte-specific gene activity and matrix properties. The NDM-grown chondrocytes in 3D cultures also showed better reproduction of deep layer properties of HC, as confirmed by microscopic and gene expression analysis. The method used in this study can yield cartilage tissue up to approximately 1.6 cm in diameter and 2 mm in thickness that satisfies the very low cell density and matrix composition properties present in the deep layer of normal HC. Conclusion: This study presents a novel and reproducible method for long-term culture of AC-derived chondrocytes and reconstruction of cartilage tissue with properties similar to the deep layer of HC in vitro. Clinical Relevance: The HC tissue obtained by the method described can be used to develop an implantable product for the replacement of damaged or malformed AC, especially in younger patients where the lesions are caused by trauma or mechanical stress.